Pengujian Hubungan Kualitas Jasa, Kepuasan Nasabah dan Intensi Pembelian Ulang. Correlation Test of Service Quality, Customer Satisfaction and Repurchase Intentions - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi Ilmu Keperawatan Fak. Kedokteran UGM, 2000)
The research is designed to examine the correlation between the service quality, customer satisfaction and purchase intentions. In details this research examines three correlation, i.e. between (1) service quality and purchase intentions